Dose uniformity of topical corticosteroid preparations: difluprednate ophthalmic emulsion 0.05% versus branded and generic prednisolone acetate ophthalmic suspension 1% - William Stringer (Dove Medical Press, 2010)
William Stringer1, Roy Bryant21Module 3 Pharma Services, St. Petersburg, Florida; 2Encompass Pharmaceutical Services, Norcross, Georgia, USAPurpose: To compare the dose uniformity of difluprednate ophthalmic emulsion 0.05% (Durezol®) with both branded and generic prednisolone acetate ophthalmic suspension 1% under different simulated patient usage conditions.Methods: Drug concentrations of difluprednate emulsion, branded prednisolone acetate suspension (Pred Forte®) and generic prednisolone acetate suspension following three storage conditions (upright, then shaken; upright, not shaken; inverted, not shaken) were analyzed by high performance liquid chromatography assay and results were reported as percent of declared concentration. Two drops were dispensed every four hours four times daily.Results: Regardless of bottle orientation and shaking, all difluprednate emulsion concentrations at each time point analyzed were within 15% of declared concentration. Both branded and generic prednisolone acetate suspension concentrations varied substantially throughout the study. For the bottle stored upright and not shaken, 46% of the branded concentrations were not within 15% of declared concentration; for the bottle stored upright and shaken prior to use, 60% failed to meet this criterion. None of the branded concentrations from the inverted and not shaken bottle was within 15% of declared concentration. Generic prednisolone concentrations demonstrated the poorest dose uniformity, with 96% of the concentrations from the inverted and not shaken bottle not within 15% of declared concentration; 94% of the concentrations from the upright and shaken bottle and 87% from the upright and not shaken bottle similarly failed to meet this criterion.Conclusions: Dose uniformity of Durezol emulsion was predictable in all simulated patient usage conditions, whereas the drop concentrations of Pred Forte and generic prednisolone acetate suspensions were highly variable throughout the study. Drop concentrations are more predictable with Durezol emulsion than with either prednisolone acetate suspension.Keywords: difluprednate, dose uniformity, emulsion, prednisolone acetate